Asia and the First World War involvement and aftermath an essay - Tarling, Nicholas (Auckland, New Zealand New Zealand Asia Institute, 2014)
This book is intended to acknowledge the involvement of Asia and Asian people in what became the first world war, and to indicate the impact on them of the war and of the peace-making. The empires in Europe were destroyed and the European empires in Asia were weakened.
Includes bibliographical references
Keywords: World War, 1914-1918.; World War, 1914-1918 -- Asia; Asia -- Politics and government; Asia -- History